Rate of change of centroidal angular momentum quantifies postural instability - Goswami, A. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Despite recent advances, the modeling, analysis, prediction and control of human postural stability remain a subject of much research interest. At the most fundamental level postural balance refers to the rotational stability of the overall human body. Based on the mechanics of multi-body systems, this paper suggests the use of Hg, the rate of change of centroidal angular momentum as a quantity for the general analysis of postural balance.